2019
DOI: 10.56338/mppki.v2i3.626
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko Kejadian Demam Berdarah Dengue (DBD) di Kabupaten Indramayu

Abstract: Demam Berdarah Dengue (DBD) merupakan salah satu masalah kesehatan di negara berkembang dan global. Penyakit DBD dikenal juga dengan istilah Dengue Haemoragic Fever (DHF), merupakan penyakit infeksi akut menular kepada manusia melalui perantara gigitan nyamuk Aedes yang mengandung virus dengue. Tujuan penelitian untuk mengetahui faktor risiko kejadian demam berdarah dengue (DBD) di Kabupaten Indramayu. Jenis penelitian ini adalah penelitian observasional analitik dengan menggunakan rancang bangun case control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
1
1
0
6
Order By: Relevance
“…Novrita et al (2017) in his research in the Work Area of the Celikah Health Center, Ogan Komering Ilir Regency, showed that there was an influence between the habit of hanging clothes and the incidence of dengue fever. In addition, this research is also in line with Akbar et al (2019) in their research showing that there is an influence of the habit of hanging clothes on the incidence of dengue hemorrhagic fever so that the habit of hanging clothes is one of the risk factors for the incidence of dengue hemorrhagic fever in Indramayu Regency. Respondents who are exposed to dengue hemorrhagic fever have a risk of 3,470 times in respondents who have the habit of hanging clothes than those who do not have the habit of hanging clothes.…”
Section: The Influence Of Hanging Clothes On the Incidence Of Dhfsupporting
confidence: 84%
“…Novrita et al (2017) in his research in the Work Area of the Celikah Health Center, Ogan Komering Ilir Regency, showed that there was an influence between the habit of hanging clothes and the incidence of dengue fever. In addition, this research is also in line with Akbar et al (2019) in their research showing that there is an influence of the habit of hanging clothes on the incidence of dengue hemorrhagic fever so that the habit of hanging clothes is one of the risk factors for the incidence of dengue hemorrhagic fever in Indramayu Regency. Respondents who are exposed to dengue hemorrhagic fever have a risk of 3,470 times in respondents who have the habit of hanging clothes than those who do not have the habit of hanging clothes.…”
Section: The Influence Of Hanging Clothes On the Incidence Of Dhfsupporting
confidence: 84%
“…Penyakit demam berdarah ini dapat menyerang pada pembuluh darah dengan manifestasi klinis dapat berupa demam dengue dan DBD. (3) Menurut WHO sejak tahun 1968 hingga 2009 tercatat negara Indonesia terdapat kasus demam berdarah dengue (DBD) tertinggi di Asia Tenggara. (4) Di Indonesia, jumlah kasus demam berdarah dengue tahun 2020 sebanyak 108.303 kasus.…”
Section: Pendahuluanunclassified
“…Pendarahan disebabkan oleh gangguan virus pada sistem pembekuan darah dan kapiler. Tanda klinis penyakit infeksi dengue dapat berupa demam berdarah dan DBD (3) . Secara umum, seseorang yang terkena DBD menunjukkan gejala pertama terjadi empat sampai enam hari setelah terkena gigitan nyamuk Aedes aegypti, namun dapat…”
Section: Pendahuluanunclassified